PLANTATION METHODS EFFECTS ON COMMON VALERIAN (VALERIANA OFFICINALIS) YIELD AND QUALITY - J. Wiśniewski; M. Szczepanik; B. Kołodziej; B. Król (Journal of Animal and Plant Sciences, 2016)
The study aimed at determination of the optimum conditions for high yielding and high quality of Valeriana officinalis L. production by selecting the best variety and plantation establishment method. A higher content of active substances but lower yields of underground parts of plants were obtained in a thin-rooted variety (‘Polka’) culture, whereas an adverse tendency was observed in a thick-rooted cultivar (‘Lubelski’). Raw material from plants produced by direct seeding was characterised by a higher content of active substances and, despite lower yields, it should be recommended in high quality valerian culture. Plants grown from the seedlings produced higher yields; however, their quality expressed by the content of valerenic acid (VA) was lower. The highest yield was obtained from seedlings planted in autumn (with a satisfactory content of VA) and therefore the method could be used for valerian plantation establishment. A positive correlation was found between the content of essential oils and VA; hence, varieties with higher essential oil accumulation should be chosen for commercial cultivation of this species. Greater accumulation of VA and essential oils was observed in dried roots separated from the underground parts of the plants prior to drying in comparison to the rhizomes.
Keywords: essential oil; variety; seedbed; sowing; multi-cell trays; valerenic acid